Do specific antimicrobial stewardship interventions have an impact on carbapenem resistance in Gram-negative bacilli? A multicentre quasi-experimental ecological study: time-trend analysis and characterization of carbapenemases. (26th March 2021) - Álvarez-Marín, Rocío; López-Cerero, Lorena; Guerrero-Sánchez, Francisca; Palop-Borras, Begoña; Rojo-Martín, María Dolores; Ruiz-Sancho, Andrés; Herrero-Rodríguez, Carmen; García, María Victoria; Lazo-Torres, Ana María; López, Inmaculada; Martín-Hita, Lina; Nuño-Álvarez, Enrique; et al.
Abstract: Background: Carbapenem-resistant Gram-negative bacilli (CR-GNB) are among the most threatening microorganisms worldwide and carbapenem use facilitates their spread. Antimicrobial stewardship programmes (ASPs) can help to optimize the use of antibiotics. This study evaluates the impact of a multifaceted educational ASP on carbapenem use and on the epidemiology of CR-GNB. Methods: We conducted a quasi-experimental, time-series study in seven hospitals, from January 2014 to September 2018. The key intervention was composed of educational interviews promoting the appropriate use of carbapenems. The primary endpoints were carbapenem consumption and incidence density (ID) of CR-GNB. All non-duplicated CR-GNB clinical isolates were tested using phenotypic assays and PCR for the presence of carbapenemases. Joinpoint regression and interrupted time-series analyses were used to determine trends. Results: A decrease in carbapenem consumption throughout the study period [average quarterly percentage change (AQPC) −1.5%, P  < 0.001] and a −8.170 (−16.064 to −0.277) level change following the intervention were observed. The ID of CR- Acinetobacter baumannii decreased (AQPC −3.5%, P   =  0.02) and the overall ID of CR-GNB remained stable (AQPC −0.4%, P   =  0.52). CR-GNB, CR- Pseudomonas aeruginosa and CR- A. baumannii IDs per hospital correlated with the local consumption of carbapenems. The most prevalent carbapenem resistance mechanisms were OXA-23 for CR- A. baumannii (76.1%), OXA-48 for CR- Klebsiella pneumoniae (66%) and no carbapenemases for CR- P. aeruginosa (91.7%). The epidemiology of carbapenemases was heterogeneous throughout the study, especially for carbapenemase-producing Enterobacteriaceae. Conclusions: In conclusion, a multifaceted, educational interview-based ASP targeting carbapenem prescribing reduced carbapenem use and the ID of CR- A. baumannii .